Insights into the structure and assembly of the Bacillus subtilis clamp-loader complex and its interaction with the replicative helicase. - Afonso, José P.; Chintakayala, Kiran; Suwannachart, Chatrudee; Sedelnikova, Svetlana; Giles, Kevin; Hoyes, John B.; Soultanas, Panos; Rafferty, John B.; Oldham, Neil J. (Oxford Journals, 2013)
The clamp-loader complex plays a crucial role in DNA replication by loading the β-clamp onto primed DNA to be used by the replicative polymerase. Relatively little is known about the stoichiometry, structure and assembly pathway of this complex, and how it interacts with the replicative helicase, in Gram-positive organisms. Analysis of full and partial complexes by mass spectrometry revealed that a hetero-pentameric τ3-δ-δ’ Bacillus subtilis clamp-loader assembles via multiple pathways, which differ from those exhibited by the Gram-negative model E. coli. Based on this information a homology model of the Bacillus subtilis τ3-δ-δ' complex was constructed, which revealed the spatial positioning of the full C-terminal τ domain. The structure of the δ subunit was determined by X-ray crystallography and shown to differ from that of E. coli in the nature of the amino acids comprising the τ and δ' binding regions. Most notably, the τ-δ interaction appears to be hydrophilic in nature compared to the hydrophobic interaction in E. coli. Finally, the interaction between τ3 and the replicative helicase DnaB was driven by ATP/Mg2+ conformational changes in DnaB and evidence is provided that hydrolysis of one ATP molecule by the DnaB hexamer is sufficient to stabilise its interaction with τ3.